2015
DOI: 10.1007/s00038-015-0768-6
|View full text |Cite
|
Sign up to set email alerts
|

School life expectancy and risk for tuberculosis in Europe

Abstract: Objective: This study aims to investigate the effect of country-level school life expectancy on Tuberculosis (TB) incidence to gain further understanding of substantial variation in TB incidence across Europe.Methods: An ecological study examined the prospective association between baseline countrylevel education in 2000 measured by school life expectancy and TB incidence in 2000-2010 in 40 countries of the WHO European region using quantile regression. Subsequently, to validate the ecological associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…A escolaridade é importante determinante em saúde, visto que interfere direta e indiretamente no estilo de vida, no padrão alimentar, nos hábitos saudáveis e no acesso aos serviços e saúde. (26) Dessa forma, utilizar a tecnologia educacional para instrumentalizar adolescentes estudantes sobre a tuberculose pode ser uma estratégia de melhoria dos indicadores epidemiológicos e de monitoramento da doença, contribuindo para alcance das metas estabelecidas pelo Plano Nacional pelo Fim da Tuberculose como Problema de Saúde. (27) Os resultados deste estudo podem contribuir para a prática de profissionais da área da saúde e da educação, como suporte para ações educativas, em especial com adolescentes, que guardem semelhança com o perfil dos participantes, podendo ser multiplicadores do conhecimento, divulgando informações corretas sobre a tuberculose.…”
Section: Discussionunclassified
“…A escolaridade é importante determinante em saúde, visto que interfere direta e indiretamente no estilo de vida, no padrão alimentar, nos hábitos saudáveis e no acesso aos serviços e saúde. (26) Dessa forma, utilizar a tecnologia educacional para instrumentalizar adolescentes estudantes sobre a tuberculose pode ser uma estratégia de melhoria dos indicadores epidemiológicos e de monitoramento da doença, contribuindo para alcance das metas estabelecidas pelo Plano Nacional pelo Fim da Tuberculose como Problema de Saúde. (27) Os resultados deste estudo podem contribuir para a prática de profissionais da área da saúde e da educação, como suporte para ações educativas, em especial com adolescentes, que guardem semelhança com o perfil dos participantes, podendo ser multiplicadores do conhecimento, divulgando informações corretas sobre a tuberculose.…”
Section: Discussionunclassified
“…Population movement creates new environments and challenges for the control of infectious diseases. As immigrants and long-stay travelers or workers become a larger part of the social population, the impact of potential infections on public health could become an important issue in the region, with a focus on prevention or early detection [35,36]. At present, China still has a number of patients with poor access to new and effective diagnoses and treatments, and with limited financial protection [37,38].…”
Section: Hsr Impacts On Tb and Healthmentioning
confidence: 99%
“…The fifth national TB survey conducted in 2010 showed that the prevalence of active TB was 459/100,000 when compared with the prevalence of 466/100,000 in 2000, however, it is estimated that 44.5% of China’s population were infected with TB [ 2 ], which represents an enormous challenge to the public health. Many researchers pointed out that students were at high risk for TB infection [ 3 ]. According to the data from National Internet-based Infectious Disease Reporting System in 2014, 4.02% of TB patients were students and the incidence of school TB was 20.16/10 5 (41,608/206,339,584) in China [ 4 ].…”
Section: Introductionmentioning
confidence: 99%